1999
DOI: 10.2165/00003495-199957010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Antihistamines

Abstract: Second-generation histamine H1 receptor antagonists (antihistamines) have been developed to reduce or eliminate the sedation and anticholinergic adverse effects that occur with older H1 receptor antagonists. This article evaluates second-generation antihistamines, including acrivastine, astemizole, azelastine, cetirizine, ebastine, fexofenadine, ketotifen, loratadine, mizolastine and terfenadine, for significant features that affect choice. In addition to their primary mechanism of antagonising histamine at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(108 citation statements)
references
References 110 publications
0
107
0
1
Order By: Relevance
“…Marked affinity of cetirizine for peripheral histamine H1 receptors results in anti-allergic properties, but has the advantage that it lacks the CNS depressant effects often encountered in anti-histamines. Cetirizine is a potent and well tolerated nonsedating antihistamine drug for the treatment of seasonal and prennial allergic rhinitis and chronic urticarial (Slater et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Marked affinity of cetirizine for peripheral histamine H1 receptors results in anti-allergic properties, but has the advantage that it lacks the CNS depressant effects often encountered in anti-histamines. Cetirizine is a potent and well tolerated nonsedating antihistamine drug for the treatment of seasonal and prennial allergic rhinitis and chronic urticarial (Slater et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue distribution studies in rats revealed that fexofenadine does not cross the blood-brain barrier [24,25]. We used fexofenadine in this study because it is very selective for H 1 receptor and only occupied peripheral histamine H 1 receptors, whereas chlorpheniramine as a firstgeneration of antihistamines have been attributed to poor H 1 -receptor specificity and also easily crossing the blood-brain barrier (BBB) and acts on the both peripheral and central receptors [26]. Cetirizine is a second-generation antihistamine with reduced brainpenetrating activity and more H 1 binding selectivity in comparison with the first-generation of antihistamine [26].…”
Section: Discussionmentioning
confidence: 99%
“…We used fexofenadine in this study because it is very selective for H 1 receptor and only occupied peripheral histamine H 1 receptors, whereas chlorpheniramine as a firstgeneration of antihistamines have been attributed to poor H 1 -receptor specificity and also easily crossing the blood-brain barrier (BBB) and acts on the both peripheral and central receptors [26]. Cetirizine is a second-generation antihistamine with reduced brainpenetrating activity and more H 1 binding selectivity in comparison with the first-generation of antihistamine [26]. Tashiro et al (2002) reported that the administration of cetirizine 20 mg/kg in the human subjects could cause occupation of 30% of histamine H 1 receptors in the cerebral cortex [25].…”
Section: Discussionmentioning
confidence: 99%
“…H 1 receptors are found on nerve endings, and distributed in the brain, smooth muscle and glandular cells, endothelial cells, the adrenal medulla and heart. 25 Since their inception, first generation antihistamines remain one of the most widely used classes of drugs in the world. Diphenhydramine, chlorpheniramine, hydroxyzine, brompheniramine, and doxylamine are included in this class.…”
Section: Antihistaminesmentioning
confidence: 99%
“…Other mechanisms that differ from the first generation antihistamines are thought to include inhibition of calcium ion influx across the mast cells thus preventing mediator release. 25 In terms of tolerability, the nonsedating antihistamines have been shown to have similar side effect profiles as placebo and are less impairing with respect to sleep, EEG, cognitive performance and anticholinergic side effects. 33 Furthermore, since newer agents are efficacious, cetirizine, fexofenadine, and loratadine are logical choices for treating allergic rhinitis in pediatric patients < 12 years of age.…”
Section: Second Generation Antihistaminesmentioning
confidence: 99%